2015
DOI: 10.3402/jchimp.v5.26586
|View full text |Cite
|
Sign up to set email alerts
|

A profile of Latinos with poorly controlled diabetes in South Florida

Abstract: IntroductionLatinos are the largest minority group in the United States and diabetes or pre-diabetes affects more than 70% of Latinos aged 45 years and older. Miami-Dade County is home to one of the highest populations of diverse Latinos. In this descriptive manuscript, we present baseline characteristics of participants enrolled in the Miami Healthy Heart Initiative (MHHI). This was a study conducted to determine the effects of a community health worker (CHW) intervention among Latinos with poorly controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Baseline characteristics of participants are provided in Table 1. Additional characteristics have been previously published . With respect to Latino ancestry, 115 (38.3%) were born in Cuba; the rest were from more than a dozen different Latin American countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline characteristics of participants are provided in Table 1. Additional characteristics have been previously published . With respect to Latino ancestry, 115 (38.3%) were born in Cuba; the rest were from more than a dozen different Latin American countries.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 212 participants, or 70.7% of our population, had positive findings on screening for depression. Helping a predominantly uninsured population find high-quality culturally acceptable behavioral and mental health services was a major challenge . The CHWs were trained to screen for depression by using standardized instruments and on the processes and procedures to link patients with the mental health resources that exist in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of depression in Hispanics with T2D are even higher. A recent study in Hispanics in South Florida showed 80% of participants met criteria for depression, while 80% and 83% of participants reported poor self-efficacy and non-adherence, respectively [ 60 ]. In other Hispanic populations, patients with depression were more likely to be non-adherent [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A survey of residents showed they were less likely than primary care practitioners to be in concordance with guidelines published by the American Thyroid Association ( 1 ). A profile of Latino patients in Dade County, Florida, demonstrated that poorly controlled diabetes was very common and associated with depression and medication non-adherence ( 2 ). There are two medical education quality improvement papers: the Modified Early Warning System (MEWS) ( 3 ) and an accompanying editorial ( 4 ), and the Transitions of Care Rotation (TRACER) outcomes paper ( 5 ).…”
mentioning
confidence: 99%